The Impact of Providing Psychological Stimulus on Improvement Cognitive Ability of Stunted Children Under 36 Months of Age - Wiyono, Sugeng; Siti Rahmawati; Muntikah; Indra Gunawan; Miranti (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2024)
The 2022 study found that 21.6% stunting. Six million short toddlers risk losing 10 - 15 points of intelligence, requiring 300-400 trillion to recover. Vocabulary scores of short children are 16.1% lower and 48.8%. The balance of growth and development and the first two years have 20 points higher intelligence. Brain volume reaches 70-80% at the beginning of life; the brain of a three-month-old baby forms a double adult connection of about 1000 trillion through psychological stimulation, observation, hearing, sensing, and movement. The study aimed to determine the benefits of providing psychological stimulation of knowledge. Using a quasi-experimental design, the population of children aged 24-36 with a sample of 24 children was determined by census. The inclusion criteria were children under three years of age with no postural abnormalities. Exclusion criteria were suffering from mental disorders. There was an increase (p=0.000) of 3.20833 ±2.84344 cognitive points. In the first week, the average cognitive score of 10.8 points increased to 14.0 points. In week four, there was a difference of 1.02857 ± 0.93348 points (p=0.057) in gender-based knowledge. When differentiated by age group, there was a difference of 0.7111 ± 0.96465 points (p=0.107). In the first week, the children felt afraid and reluctant and did not dare to show their abilities, and the provision of psychological stimulation changed. The child is easy to interact with and does not hesitate to say names or make movements. There is an increase in cognitive ability of 3.20833 ± 2.84344 points. It is recommended that psychological stimulation is given to increase knowledge.